Identification of an immunodominant region on a group A Streptococcus T-antigen reveals temperature-dependent motion in pili. Issue 1 (31st December 2023) - Raynes, Jeremy M.; Young, Paul G.; Lorenz, Natalie; Loh, Jacelyn M.S.; McGregor, Reuben; Baker, Edward N.; Proft, Thomas; Moreland, Nicole J.
ABSTRACT: Group A Streptococcus (GAS) is a globally important pathogen causing a broad range of human diseases. GAS pili are elongated proteins with a backbone comprised repeating T-antigen subunits, which extend from the cell surface and have important roles in adhesion and establishing infection. No GAS vaccines are currently available, but T-antigen-based candidates are in pre-clinical development. This study investigated antibody-T-antigen interactions to gain molecular insight into functional antibody responses to GAS pili. Large, chimeric mouse/human Fab-phage libraries generated from mice vaccinated with the complete T18.1 pilus were screened against recombinant T18.1, a representative two-domain T-antigen. Of the two Fab identified for further characterization, one (designated E3) was cross-reactive and also recognized T3.2 and T13, while the other (H3) was type-specific reacting with only T18.1/T18.2 within a T-antigen panel representative of the major GAS T-types. The epitopes for the two Fab, determined by x-ray crystallography and peptide tiling, overlapped and mapped to the N-terminal region of the T18.1 N-domain. This region is predicted to be buried in the polymerized pilus by the C-domain of the next T-antigen subunit. However, flow cytometry and opsonophagocytic assays showed that these epitopes were accessible in the polymerized pilus at 37°C, though not at lower temperature. This suggests that there is motion within the pilus at physiological temperature, with structural analysis of a covalently linked T18.1 dimer indicating "knee-joint" like bending occurs between T-antigen subunits to expose this immunodominant region. This temperature dependent, mechanistic flexing provides new insight into how antibodies interact with T-antigens during infection.